Recent progress on organic donor-acceptor complexes as active elements in organic field-effect transistors - Zhang, Jing (2020)
Recently, organic donor–acceptor complexes (co-crystals) have been strongly explored as active elements in organic field-effect transistors (OFETs) due to their tunable energy level and different stacking modes. The performance of co-crystal-based FETs can be enhanced through the design and synthesis of novel complexes, the control of the self-assembling morphology of co-crystals on substrates, and the optimization of the fabrication conditions of devices. In this review, we will summarize the recent progress on the methods to prepare donor (D)–acceptor (A) co-crystals and their films, present their structure–property relationships, and discuss their potential applications in OFETs according to the co-crystals with different acceptors, namely, (a) tetracyanoquinodimethane (TCNQ) and derivatives; (b) fullerene derivatives (such as C60 and C70); and (c) naphthalenediimide and perylenediimide derivatives. Moreover, co-crystal-based solid solutions and their FET performance are also mentioned.